Coupling Solvent Extraction Units to Cyclic Adsorption Units - Mariana Busto; Enrique Eduardo Tarifa; Carlos Román Vera (International Journal of Chemical Engineering)
The possibility of regenerating the solvent of extraction units by cyclic adsorption was analyzed. This combination seems convenient when extraction is performed with a high solvent-to-impurity ratio, making other choices of solvent regeneration, typically distillation, unattractive. To our knowledge, the proposed regeneration scheme has not been considered before in the open literature. Basic relations were developed for continuous and discontinuous extraction/adsorption combinations. One example, deacidification of plant oil with alcohol, was studied in detail using separate experiments for measuring process parameters and simulation for predicting performance at different conditions. An activated carbon adsorbent was regenerated by thermal swing, making cyclic operation possible. When extracting the acid with methanol in a spray column, feed = 4 L min−1, solvent = 80 L min−1, feed impurity level 140 mmol L−1, and extract concentration 7.6 mmol L−1, the raffinate reaches a purity of 1.2 mmol L−1, the solvent being regenerated cyclically in the adsorber (364 kg) to an average of 0.7 mmol L−1. Regeneration of the solvent by cyclic adsorption had a low heat duty. Values of 174 kJ per litre of solvent compared well with the high values for vaporization of the whole extract phase (1011 kJ L−1).